Infection prevention in breast cancer patients with neutropenia undergoing neoadjuvant paclitaxel - carboplatin chemotherapy: a case study - Nuraini, Ditra Cholidy; Haryani; Suparno, Agus (Sahabat Publikasi Kuu, 2023)
Background : One of the side effects of chemotherapy related to hematology can be neutropenia. Neutropenia can occur in patients receiving chemotherapy with a combination of taxan and platinum regimens, such as Paclitaxel and Carboplatin. Loss of neutrophils can cause disruption of the immune defense mechanism and increase the risk of infection in patients. So it is necessary to prevent infection both pharmacologically and non-pharmacologically. Objective : To describe neutropenia in breast cancer patients undergoing neoadjuvant paclitaxel and carboplatin chemotherapy, as well as actions that can be taken to prevent infection in patients. Case Description : A 35-year-old patient, with a medical diagnosis of positive HER2 ductal mammary gland left and experienced severe neutropenia with a neutrophil count # or ANC (absolute neutrophil count) 0.021 x 103/µL. During treatment, prevention of infection is carried out by giving leucogene, washing hands, applying aseptic techniques, using PPE, and monitoring signs and symptoms of infection. In addition, the cleanliness of the environment around the patient must be maintained and environmental modifications can be made. As well as providing education to patients and families regarding hand washing, nutritional intake, and limiting the number of families. Conclusion : Severe neutropenia in breast cancer patients undergoing chemotherapy can increase the risk of infection. There are several actions that can be taken by patients and their families, health workers, especially nurses, as well as by managing the surrounding environment to prevent infection in patients.